Nurse mothers valuing care at home and at work: Beyond notions of care scarcity?. (December 2014) - Maher, JaneMaree
Contemporary discussions about family care in western societies are generally framed in discourses of scarcity, as changing social structures put pressure on how parental care is delivered while paid care workers face time pressures and deficits in workplaces. From a recent study of nursing families in Australia, I focus on the care practices of mothers who are also nurses. I examine how these female nurses understood and managed competing care pressures across work and family boundaries. Rather than experiencing only care scarcity and pressure, these women maintained a consistent sense of the importance of care in both domains, which informed and supported both their family and work practices. The demand to give care in both domains did not necessarily deplete their capacity for care. Rather, they created a set of congruent care ideals and practices at work and home, and maintained the importance and value of caring labour in their daily lives.